Core–Shell–Satellite Nanomaces as Remotely Controlled Self‐Fueling Fenton Reagents for Imaging‐Guided Triple‐Negative Breast Cancer‐Specific Therapy. Issue 31 (9th June 2020) - Du, Yang; Yang, Chuang; Li, Fangyuan; Liao, Hongwei; Chen, Zheng; Lin, Peihua; Wang, Nan; Zhou, Yan; Lee, Ji Young; Ding, Qiang; Ling, Daishun
Abstract: Triple‐negative breast cancer (TNBC) is highly aggressive and insensitive to conventional targeted therapies, resulting in poor therapeutic outcomes. Recent studies have shown that abnormal iron metabolism is observed in TNBC, suggesting an opportunity for TNBC treatment via the iron‐dependent Fenton reaction. Nevertheless, the efficiency of current Fenton reagents is largely restricted by the lack of specificity and low intracellular H2 O2 level of cancer cells. Herein, core–shell–satellite nanomaces (Au @ MSN@IONP) are fabricated, as near‐infrared (NIR) light‐triggered self‐fueling Fenton reagents for the amplified Fenton reaction inside TNBC cells. Specifically, the Au nanorod core can convert NIR light energy into heat to induce massive production of intracellular H2 O2, thereby the surface‐decorated iron oxide nanoparticles (IONP) are being fueled for robust Fenton reaction. By exploiting the vulnerability of iron efflux in TNBC cells, such a self‐fueling Fenton reaction leads to highly specific anti‐TNBC efficacy with minimal cytotoxicity to normal cells. The PI3K/Akt/FoxO axis, intimately involved in the redox regulation and survival of TNBC, is demonstrated to be inhibited after the treatment. Consequently, precise in vivo orthotopic TNBC ablation is achieved under the guidance of IONP‐enhanced magnetic resonance imaging. The results demonstrate the proof‐of‐concept of NIR‐light‐triggered self‐fueling Fenton reagents against TNBC with low ferroportin levels. Abstract : Core–shell–satellite nanomaces are fabricated by decorating ultrasmall iron oxide nanoparticles (IONPs) onto silica‐coated Au nanorods. Upon near‐infrared irradiation, the elevation of intracellular H2 O2 is induced by photothermal conversion, fueling the IONPs‐catalyzed Fenton reaction to generate cytotoxic hydroxyl radicals. Utilizing the vulnerability of iron efflux in triple‐negative breast cancer (TNBC) cells, the self‐fueling Fenton reagents exhibit highly TNBC‐specific therapy.